The white-nosed coati (Nasua narica) is a naturally susceptible definitive host for the zoonotic nematode Angiostrongylus costaricensis in Costa Rica - Hagnauer, Isabel (2016)
Angiostrongylus costaricensis (Strongylida, Angiostrongylidae) is a roundworm of rodents, which may cause a severe or fatal zoonosis in several countries of the Americas. A single report indicated that the white-nosed coati (Nasua narica), acts as a potential free-ranging wildlife reservoir. Here we investigated the prevalence and features of A. costaricensis infection in two procyonid species, the white-nosed coati and the raccoon (Procyon lotor) from Costa Rica to better understand their possible role in the epidemiology of this zoonotic infection. Eighteen of 32 (56.2%) white-nosed coatis collected between July 2010 and March 2016 were infected with A. costaricensis but none of 97 raccoons from the same localities were diagnosed with this infection. First-stage larvae of A. costaricensis were obtained from feces of 17 fresh white-nosed coati carcasses by Baermann technique. Parasite identity was confirmed by morphology, histology and molecular characterization of target genes. These data demonstrate that the white-nosed coati is a naturally susceptible definitive host for A. costaricensis in Costa Rica contrary to findings in the raccoon.